ANALISIS PENGUKURAN KINERJA PUSKESMAS PEGIRIAN KOTA SURABAYA DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD - Nurmandhani, Ririn; Ayu Pradita, Dhea; Rimawati, Eti; Ana Veria Setyawati, Vilda (VISIKES, 2024)
Puskesmas Pegirian, Surabaya, in several aspects was still in the less than good category in 2022. This research aims to determine the performance of Puskesmas Pegirian based on four balanced scorecard perspectives. This type of research was quantitative descriptive with a sampling technique using a quota sampling technique, namely with predetermined inclusion and exclusion criteria. The data collection technique was carried out using a questionnaire distributed to officer respondents and patient respondents. The results of the study show that the performance of the Puskesmas Pegirian when viewed from four balanced scorecard perspectives was in the fairly good category, namely 50%. The results of this study were influenced by the financial perspective and customer perspective as internal aspects and the internal business process perspective and the growth and income perspective as external aspects. In this study, there was an imbalance where the health center tended to focus more on the internal aspects, namely with a total score of 3 while the external aspects had a total score of 2. Therefore, it is necessary to evaluate and improve the four perspectives that have not yet reached the target. So that in further research there can be improvements in each aspect.